Comparison of computational model and X-ray crystal structure of human serotonin transporter: potential application for the pharmacology of human monoamine transporters. Issue 13 (2nd November 2017) - Yang, Fengyuan; Fu, Tingting; Zhang, Xiaoyu; Hu, Jie; Xue, Weiwei; Zheng, Guoxun; Li, Bo; Li, Yinghong; Yao, Xiaojun; Zhu, Feng
Abstract: The human serotonin transporter (hSERT) played a significant role in neurological process whose structural basis had been analysed for many years. Recently, the first homology model was constructed for hSERT based on the crystal structure of drosophila melanogaster dopamine transporter was published, and the inhibitory mechanism underlying the binding mode between hSERT and approved antidepressants was substantially investigated by molecular dynamics (MD) simulation. Right after this publication, the X-ray crystallographic structures of hSERT were reported, which provided a good opportunity to reassess the performance of previous simulation. In this study, the analyses of side-chain contact map, stereochemical quality and ligand-binding pocket were firstly conducted, which revealed that the constructed homology model of hSERT could successfully reproduce the reported crystal structure. Secondly, the approved antidepressant escitalopram was docked into the X-ray structure, and its binding pose was consistent with the reported docking pose in the homology model. Finally, MD simulation were performed based on the crystal structure of hSERT, and structural features revealed as critical for escitalopram-hSERT interaction by previous simulation were successfully recaptured. Thus, the newly reported X-ray crystal structure of hSERT was precisely predicted by computational model, which demonstrated its reliability in understanding the pharmacology of other human monoamine transporters whose 3-D structure remained unknown.